Regulation of protein function by reversible methionine oxidation and the role of selenoprotein MsrB1 - Kaya, Alaattin; Lee, Byung Cheon; Gladyshev, Vadim N (Antioxidants & redox signaling, 2015)
Protein structure and function can be regulated via post-translational modifications by numerous enzymatic and nonenzymatic mechanisms. Regulation involving oxidation of sulfur-containing residues emerged as a key mechanism of redox control. Unraveling the participants and principles of such regulation is necessary for understanding the biological significance of redox control of cellular processes. Reversible oxidation of methionine residues by monooxygenases of the Mical family and subsequent reduction of methionine sulfoxides by a selenocysteine-containing methionine sulfoxide reductase B1 (MsrB1) was found to control the assembly and disassembly of actin in mammals, and the Mical/MsrB pair similarly regulates actin in fruit flies. This finding has opened up new avenues for understanding the use of stereospecific methionine oxidation in regulating cellular processes and the roles of MsrB1 and Micals in regulation of actin dynamics. So far, Micals have been the only known partners of MsrB1, and actin is the only target. It is important to identify additional substrates of Micals and characterize other Mical-like enzymes. Oxidation of methionine, reviewed here, is an emerging but not well-established mechanism. Studies suggest that methionine oxidation is a form of oxidative damage of proteins, a modification that alters protein structure or function, a tool in redox signaling, and a mechanism that controls protein function. Understanding the functional impact of reversible oxidation of methionine will require identification of targets, substrates, and regulators of Micals and Msrs. Linking the biological processes, in which these proteins participate, might also lead to insights into disease conditions, which involve regulation of actin by Micals and Msrs.